Single large or several small? The influence of prey size on feeding performance of Philodryas nattereri (Squamata: Serpentes) - Sara Catunda Pereira; João Fabrício Mota Rodrigues; Diva Maria Borges-Nojosa (Acta Scientiarum. Biological Sciences, 2016)
This study aimed at evaluating the energetic return and feeding time on Philodryas nattereri kept in captivity. Snakes were fed biweekly for 60 days (four feeding trials), in two different feeding treatments (single and multiple prey items). The energetic return revealed no significant difference between the feeding treatments; however, we found a negative relationship between snake size and prey handling time during a feed using multiple prey items. In P. nattereri, when large preys are as easy to find as small ones, there seems to be no difference in energetic return.